Fabrication of Poly-l-lactic Acid/Dicalcium Phosphate Dihydrate Composite Scaffolds with High Mechanical Strength—Implications for Bone Tissue Engineering - Nida Tanataweethum; Wai Ching Liu; W. Scott Goebel; Ding Li; Tien Min Chu (Journal of Functional Biomaterials, 2015)
Scaffolds were fabricated from poly-l-lactic acid (PLLA)/dicalcium phosphate dihydrate (DCPD) composite by indirect casting. Sodium citrate and PLLA were used to improve the mechanical properties of the DCPD scaffolds. The resulting PLLA/DCPD composite scaffold had increased diametral tensile strength and fracture energy when compared to DCPD only scaffolds (1.05 vs. 2.70 MPa and 2.53 vs. 12.67 N-mm, respectively). Sodium citrate alone accelerated the degradation rate by 1.5 times independent of PLLA. Cytocompatibility of all samples were evaluated using proliferation and differentiation parameters of dog-bone marrow stromal cells (dog-BMSCs). The results showed that viable dog-BMSCs attached well on both DCPD and PLLA/DCPD composite surfaces. In both DCPD and PLLA/DCPD conditioned medium, dog-BMSCs proliferated well and expressed alkaline phosphatase (ALP) activity indicating cell differentiation. These findings indicate that incorporating both sodium citrate and PLLA could effectively improve mechanical strength and biocompatibility without increasing the degradation time of calcium phosphate cement scaffolds for bone tissue engineering purposes.